Walsh, C. Gender discourse. language and power in politics, the church and organisations. Londres: Longman, 2001, 236 págs. - Lima, Maria Cecília de (Cadernos de Linguagem e Sociedade, 2010)
Walsh, C. Gender discourse. language and power in politics, the church and organisations. Londres: Longman, 2001, 236 págs.